Bitch in Heat of a Red Dream: from Revolution to Becoming. Reflections from a Practical Aesthetics on the Possibility of a Contemporary Subject and Politics - Luzza Rodríguez, Pablo (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The problem of politics in contemporary social theory confronts us with the tension between political action capable of social transformation, and the dissolution of the subject. If there is neither subject, nor authors, personalities or leaders, in the modern conception of these terms, what sort of social and political actions would be able to change the course of history? Considering the notion of ‘anal politics’ proposed by Paul B. Preciado, this article concentrates its analysis on queer theories and practices, in order to offer a possible reading of the relation between micro and macropolitical processes and their implication on the production of subjects, as well as artistic and cultural creativity. The Argentinian ar- tivist poet Susy Shock, of manifest queer political rooting, will serve as a case study to inquire into an aesthetic-political-theorical process that challenges the social frontiers of the possible.